Internal Rent Seeking, Works Councils, and Optimal Establishment Size - Michael Beckmann; Matthias Kräkel (University of Basel, Center of Business and Economics (WWZ), 2011)
Using a microeconomic model and data from the Establishment Panel of the German Institute for Employment Research, we analyze the optimal establishment size against the background of rent-seeking workers and the influence of works councils. The theoretical part shows that establishment size has a discouragement effect on the level of individual rent seeking but also a quantity effect as the number of rent seekers increases. The interplay of both effects – together with technological considerations – determines whether the employer chooses an inefficiently small or large establishment size. Introduction of a works council restores efficient establishment size although it is purely used as rent-seeking device. Whether the employer benefits from a works council or not, depends on the degree of contract incompleteness and the degree of worker coordination via a works council. The empirical part indicates dominance of the discouragement effect over the quantity effect in establishments without works council. As theoretically predicted, works councils are beneficial by disentangling rent-seeking and production issues, thus eliminating the influence of the two rent-seeking effects.
Keywords: J51; J52; J53; L25; 330; establishment size; rent-seeking; works council; Rent-Seeking; Arbeitskräfte; Betriebsrat; Personalbestand; Betriebsgröße; Deutschland